Particle swarm optimization (PSO) to optimize an assembly sequence time [electronic resource] - Chee, Der Zhan, 1988-, author; Jameel A.A. Mukred, supervisor; Fakulti Kejuruteraan Elektrik (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mekatronik)) - Universiti Teknologi Malaysia, 2011